Beyond Digital Transparency: Do Digital and Risk Management Disclosures Improve Earnings Quality? Evidence from Indonesian Consumer Non-Cyclical Companies - Ulfa Puspa Wanti Widodo; Nanda Wahyu Indah Kirana; Rizdina Azmiyanti (Journal of Creative Power and Ambition (JCPA), 2026)
This study examined whether digital disclosure and risk management disclosure were associated with earnings quality in Indonesian consumer non-cyclical firms. The sample consisted of 86 companies and 236 unbalanced firm-year observations from 2022 to 2024. Earnings quality was proxied by absolute discretionary accruals estimated using the Modified Jones Model. Digital Disclosure Index was measured using four indicators: information, timeliness, accessibility, and technology. Risk Management Disclosure was measured using a 20-item disclosure index based on annual reports. Panel data regression was analyzed using the Random Effect Model. The results showed that Digital Disclosure Index did not significantly affect earnings quality. In contrast, Risk Management Disclosure had a negative and significant effect on absolute discretionary accruals, indicating that broader risk management disclosure improved earnings quality. This study contributes to disclosure and earnings quality literature by showing that substantive risk transparency is more relevant than basic digital disclosure compliance in explaining accrual quality.